Engineering biomimetic and instructive materials for wound healing and regeneration. (June 2019) - Chantre, Christophe O.; Hoerstrup, Simon P.; Parker, Kevin Kit
Abstract: Development of biomimetic and instructive materials is emerging as a promising approach for redirecting fibrotic wound healing into a regenerative process. In nature, complete tissue regeneration can transpire in certain organ substructures,  during embryogenesis and, remarkably, in some organisms in which whole limbs can regrow. These regenerative phenomena were observed to possess specific extracellular matrices, as well as stem cell niches and regulatory signaling pathways, that likely act as spatiotemporal organizers of these preferred outcomes. Biomimetic materials are now improving on the limitations of existing wound care treatments because they are being designed to stimulate these spatiotemporal cues, thus supporting regeneration within host tissues. A variety of novel materials have already emerged and demonstrated promise both in preclinical studies and in patients. This review discusses the recent advances in understanding these biomimetic and instructive properties and their integration into wound care scaffolds. Graphical abstract: Studies from basic cell biology and of regenerative processes in humans and other organisms have enabled key spatiotemporal mediators of tissue growth and repair to be uncovered. Biomaterials are now taking inspiration from these studies to target these regulatory mediators to improve the normal outcome of wound healing. These include biomimetic properties (mechanical, structural, and biochemical) and strategies to actively control how the material (abiotic) is going to interface and integrate within the host (biotic). Image 1